Hermann Cohen : writings on neo-Kantianism and Jewish philosophy - Moyn, Samuel; Schine, Robert S.; Cohen, Hermann, 1842-1918 (Tauber Institute for the Study of European Jewry series (Unnumbered), 2021)
"Hermann Cohen (1842-1918) was among the most accomplished Jewish philosophers of modern times. This newly translated collection of his writings illuminates his achievements for student readers and rectifies lapses in his intellectual reception by prior generations"--